Young mixed planted forests store more carbon than monocultures—a meta-analysis - Warner, Emily; Cook-Patton, Susan C.; Lewis, Owen T.; Brown, Nick; Koricheva, Julia; Eisenhauer, Nico; Ferlian, Olga; Gravel, Dominique; Hall, Jefferson S.; Jactel, Hervé; Mayoral, Carolina; Meredieu, Céline; et al. (Frontiers in Forests and Global Change, 2023)
Although decades of research suggest that higher species richness improves ecosystem functioning and stability, planted forests are predominantly monocultures. To determine whether diversification of plantations would enhance aboveground carbon storage, we systematically reviewed over 11,360 publications, and acquired data from a global network of tree diversity experiments. We compiled a maximum dataset of 79 monoculture to mixed comparisons from 21 sites with all variables needed for a meta-analysis. We assessed aboveground carbon stocks in mixed-species planted forests vs (a) the average of monocultures, (b) the best monoculture, and (c) commercial species monocultures, and examined potential mechanisms driving differences in carbon stocks between mixtures and monocultures. On average, we found that aboveground carbon stocks in mixed planted forests were 70% higher than the average monoculture, 77% higher than commercial monocultures, and c.25% higher than the best performing monocultures, although the latter was not statistically significant.Overyielding was highest in four-species mixtures (richness range 2-6 species), but otherwise none of the potential mechanisms we examined (nitrogen-fixer present vs absent; native vs non-native/mixed origin; tree diversity experiment vs forestry plantation) consistently explained variation in the diversity effects. Our results, predominantly from young stands, thus suggest that diversification could be a very promising solution for increasing the carbon sequestration of planted forests and represent a call to action for more data to increase confidence in these results and elucidate methods to overcome any operational challenges and costs associated with diversification.